Effectiveness of pay for performance to non-physician health care providers: A systematic review. Issue 7 (July 2022) - Asadi-Aliabadi, Mehran; Karimi, Seyed M; Tehrani-Banihashemi, Arash; Mirbaha-Hashemi, Fariba; Janani, Leila; Babaee, Ebrahim; Nojomi, Marzieh; Moradi-Lakeh, Maziar
Higlights: Paying to non-physician health workers could potentially improve the quality of care and other health indicators. The heterogeneity in the methods of conducting primary studies and the limited number of studies with strong designs avoids us for making strong conclusions. Sound research designs and behavioral and institutional complexities (rooted in healthcare workers' responses to incentives type, size, change, and payment method) need to be carefully considered in the design and execution of pay for performance programs.